4
$\begingroup$

Problem:Let $X$ and $Y$ be identically distributed independent random variables such that the moment generating function of $X +Y$ is $$M(t) = 0.09 e^{−2t} + 0.24 e^{−t} + 0.34 + 0.24 e^t + 0.09 e^{2t}$$ for $−\infty < t < \infty$. Calculate $P[X \le 0]$.

Answer: Because $X$ and $Y$ are independent and identically distributed, the moment generating function of $X+ Y$ equals $K^2(t)$, where $K(t)$ is the moment generating function common to $X$ and $Y$. Thus, $$K(t) = 0.30e^{-t} + 0.40 + 0.30e^t$$

This is the moment generating function of a discrete random variable that assumes the values $-1$, $0$, and $1$ with respective probabilities $0.30$, $0.40$, and $0.30$. The value we seek is thus $0.70$. My question is how to factor the moment generating function of $X+Y$ to $0.30e^-t + 0.40 + 0.30e^t$, is there a general formula to use?

I'm also sorry for not using MathJax I'm really having trouble with it.

$\endgroup$
  • $\begingroup$ I fixed the math formatting. Check if it's ok. And you should look into the edited question (press "edit") to learn by example how it's done, it's not difficult. $\endgroup$ – leonbloy Aug 11 '16 at 22:57
  • $\begingroup$ Let $u = e^t$. Start by noting that $0.09u^2 + 0.09 u^{-2} = \left(0.03 ( u + u^{-1})\right)^2 - 0.18$. Next set $u + u^{-1} = v$. You now have the quadratic $(0.03 v)^2 + 0.24 v + 0.16$, which is easy to factorise. BTW - the fact that $(x + x^{-1})^2 = x^2 + x^{-2} + 2$ is in general very useful, and should immediately enter your mind when trying to factorise expressions which have terms like $ax^2 + ax^{-2}$. $\endgroup$ – stochasticboy321 Aug 11 '16 at 23:01
  • $\begingroup$ As an aside, in this case it's possible to construct $K$ merely by inspection. You know that $X$ and $Y$ are iid, and since their sum is in $\{-2, -1, 0,1,2\}$, they must take values in $\{-1,0,1\}$. Now, the sum can only equal $-2$ if they're both $-1$, so you immediately know that $P(X = -1) = \sqrt{0.09}$, and similarly for $P(X=1)$. Normalisation will then give you $P(X=0)$. $\endgroup$ – stochasticboy321 Aug 11 '16 at 23:05
  • $\begingroup$ Thanks, I would never thought of this on the test $\endgroup$ – Theo Robinson Aug 12 '16 at 15:26
5
$\begingroup$

The factorization may be easier to detect if we let $z = e^t$ and write $$\begin{align*} M_{X+Y}(t) &= \frac{9}{100} z^{-2} + \frac{24}{100} z^{-1} + \frac{34}{100} + \frac{24}{100} z + \frac{9}{100} z^2 \\ &= \frac{1}{(10z)^2} \left( 9 + 24 z + 34 z^2 + 24 z^3 + 9 z^4 \right) \\ &= \frac{1}{(10z)^2} (3 + 4z + 3z^2)^2, \end{align*}$$ keeping in mind that you are looking for a perfect square. Alternatively, you can posit a form of the common MGF to $X$ and $Y$, observing from the powers of $e^t$ that it needs to be $$M_X(t) = M_Y(t) = az^{-1} + b + cz$$ for suitable constants $a, b, c$, then equating coefficients of $M_X (t)^2$.

$\endgroup$
  • 1
    $\begingroup$ To factor every polynomial $$p(z)=a+bz+cz^2+bz^3+az^4$$ use the change of variable $$u=z+\frac1z$$ and note that $$p(z)=z^2\,\left(a(z^2+1/z^2)+b(z+1/z)+c\right)=z^2\,\left(a(u^2-2)+bu+c\right)$$ then one can factor the quadratics in $u$, leading to $$p(z)=az^2(u-\alpha)(u-\beta)=a(z^2-\alpha z+1)(z^2-\beta z+1)$$ and now one must simply factor the quadratics $z^2-\alpha z+1$ and $z^2-\beta z+1$. If $$(a,b,c)=(9,24,34)$$ then $$a(u^2-2)+bu+c=9u^2+24u+16=(3u+4)^2$$ hence, indeed, as stated above, $$p(z)=(3z^2+4z+3)^2$$ $\endgroup$ – Did Aug 27 '16 at 10:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.